Modelling af fusioner i detailsektoren - Niels Blomgren-Hansen (Copenhagen Business School (CBS), Department of Economics, 2009)
– Modelling the eects of mergers in the retail sector. According to the Danish Competition Act, a merger that impedes ef- fective competition signi cantly, in particular by creating or strengthening a dominant postition, shall be prohibited. To decide whether this is the case the authorities need a quanti able model of the relationship between the variables that are directly aected by the merger and some measure of competition. In this paper we set up and calibrate a simple model of the inter- action of the retail and the wholesale markets based on a concrete case (the acquisition and merger of 250 shops previously organized in a vol- untary chain of shops comprising roughly half of the market for high-end cosmetics in Denmark). The model predicts that an unconditioned merger was likely to have a signi cant impact on retail prices, in particular through possible abuse of buyer-power, and that the authorities had good reasons for conditioning its approval on the removal of a number of contract-based barriers to entry. Analytically, the main results are the following: (1) In a linear model characterized by heterogenous products and constant marginal costs the optimal wholesale prices are unaected by the structure in the retail sec- tor. (2) The eect on of buyer-power induced quantity discounts depends crucially on the speci c design of the rebate scheme: A relative discount on the list price the independent shops are charged increases the average retail price; A xed reduction relative to the pre-merger price reduces the average retail price). (3) Buyer-power induced retail price maintenance (RPM) increases the average retail price. RPM increases the competitive- ness and pro ts of the merged shops if producers keep wholesale prices unchanged. If, however, the producers adjust their wholesale prices, then RMP hurts merged and independent shops alike and bene ts only the producers.
hdl:10398/7986
Keywords: D40; 330; retail trade; retail prices